Ag@AgCl nanoparticles grafted on carbon nanofiber: an efficient visible light plasmonic photocatalyst via bandgap reduction. (19th November 2022) - Thao, Vu Dinh; Dung, Nguyen Trung; Ha, Nguyen Thu; Minh, Ho Ngoc; Duong, Hung Cong; Van Nguyen, To; Son, Luong Trung; Huy, Nguyen Nhat; Thu, Tran Viet
Abstract: A novel silver@silver chloride/carbon nanofiber (Ag@AgCl/CNF) hybrid was synthesized by electrospinning, heat treament, and subsequent in situ chemical oxidation strategy. The synthesized materials were characterized using x-ray diffraction, Fourier-transform infrared, UV–Vis diffuse reflectance spectroscopy, scanning electron microscopy, and energy dispersive x-ray. The experimental results reveal that the electrospun AgNO3 /PAN was carbonized and reduced to Ag/CNF, the Ag/CNF was then partly oxidized to form Ag@AgCl/CNF in which Ag@AgCl nanoparticles (ca. 10–20 nm in diameter) were uniformly bounded to CNFs (ca. 165 nm in diameter). The obtained Ag@AgCl/CNF was employed for Na2 S2 O8 activation under visible light irradiation to treat Rhodamine B (RhB). A remarkable RhB removal of ca. 94.68% was achieved under optimal conditions, and the influence of various parameters on removal efficiency was studied. Quenching experiments revealed that HO, SO4 −, 1 O2, and O2 − were major reactive oxygen species, in which O2 − played a pivotal role in RhB degradation. A possible mechanistic route for RhB degradation was proposed.